2011
DOI: 10.1080/00071668.2010.544714
|View full text |Cite
|
Sign up to set email alerts
|

Growth response, blood characteristics and copper accumulation in organs of broilers fed on diets supplemented with organic and inorganic dietary copper sources

Abstract: 1. A 56-d experiment was conducted to study the comparative influence of organic and inorganic dietary copper (Cu) sources on growth, blood characteristics and copper accumulation in organs of broilers. 2. A total of 480 Arbor-Acre unsexed broilers were fed on diets containing copper sulphate (CuSO(4)) or copper proteinate (Cu Pro) at concentrations of 50, 100 or 150 mg/kg of Cu supplementation. The birds were given a broiler starter diet from 1-28 d and a broiler finisher diet from 29-56 d which contained 30·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Many studies (Jegede, Oduguwa, Bamgbose, Fanimo, & Nollet, ; Kumar et al., ; Payvastegan, Farhoomand, & Delfani, ; Samanta, Biswas, & Ghosh, ; Zahedi, Ghalehkandi, Ebrahimnezhad, & Emami, ) have shown a reduction in cholesterol levels after adding Cu to poultry diets, which is in agreement with our results. This can be explained, in that adding higher levels of Cu will regulate cholesterol biosynthesis indirectly by decreasing the reduced form of glutathione and increasing the oxidised form of glutathione (Bakalli, Pesti, Ragland, & Konjufca, ; Kim, Chao, & Allen, ).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies (Jegede, Oduguwa, Bamgbose, Fanimo, & Nollet, ; Kumar et al., ; Payvastegan, Farhoomand, & Delfani, ; Samanta, Biswas, & Ghosh, ; Zahedi, Ghalehkandi, Ebrahimnezhad, & Emami, ) have shown a reduction in cholesterol levels after adding Cu to poultry diets, which is in agreement with our results. This can be explained, in that adding higher levels of Cu will regulate cholesterol biosynthesis indirectly by decreasing the reduced form of glutathione and increasing the oxidised form of glutathione (Bakalli, Pesti, Ragland, & Konjufca, ; Kim, Chao, & Allen, ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, no difference in muscle copper concentrations in ewes was found when copper was given in the form of sulphate or chelated amino acid hydrate (Pal et al, 2010). The overall equivalent bioavailability of copper from both sources in terms of copper deposition is also supported by data from the tibia in chickens for fattening (Bao et al, 2007;Jegede et al, 2011).…”
Section: Copper Deposition In Tissues and Products Of Animal Originsupporting
confidence: 50%
“…Similarly, studies using a copper dose of 8 mg/kg feed (Ao et al, 2009;Aksu et al, 2010) from copper sulphate or from chelated amino acid hydrate did not result in a different pattern of copper liver deposition in chickens for fattening. Only in the study of Jegede et al (2011), in which broilers' diet was supplemented with copper at with copper supplementation levels of 50, 100 and 150 mg copper from copper sulphate or from chelated amino acid hydrate, did the highest element dose result in significantly higher copper liver deposition independent of source. However, this level of copper feed supplementation (150 mg/kg) exceeds by six times the maximum EU authorised total copper level in complete feed.…”
Section: Copper Deposition In Tissues and Products Of Animal Originmentioning
confidence: 99%
See 1 more Smart Citation
“…In laying hens, the Cu content per kg of excreta dry matter (DM) increased from 25.3 to 397 mg/kg when the basal diet was supplemented with CuSO 4 (Cu-SUL) at 0 and 240 mg/kg (Skřivan et al, 2006). In many experiments it was demonstrated that organic trace elements, including amino acid chelates, increase nutrient bioavailability (Leeson and Caston, 2008;Jegede et al, 2011) and decrease faecal nutrient losses (Mikulski et al, 2009). Amino acid chelates are absorbed from the intestines at a significantly higher rate than soluble inorganic metal salts, but their supplementation is often difficult and not economically viable (Andersen, 2004).…”
Section: Introductionmentioning
confidence: 99%